PENGEMBANGAN ELEKTRONIK MODUL BERBASIS PROBLEM BASED LEARNING PADA MATERI ZAT ADITIF DAN ZAT ADIKTIF UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Muzzazinah .; Daru Wahyuningsih; Jayanti Sinung Prabasari (Postgraduate, University of Mataram, 2021)
The purpose of this study was to determine the characteristics, feasibility, and effectiveness of the E-module of additives and addictive substances based on problem-based learning in order to improve students' ability to think critically. The type of research used is development research, which refers to the Borg and Gall development model which is modified and adapted to conditions in the field into 9 stages, namely: 1) needs analysis and information gathering, 2) potential problems in the field, 3) product design, 4) design validation, 5) product design improvement, 6) limited trial, 7) product revision, 8) operational field test, 9) E-module final product. The data analysis technique used is a descriptive analysis which is used to describe the characteristics of the developed E-module, the feasibility analysis of the E-module is based on the N-gain score obtained, the results of this study found that the problem-based learning-based E-module has been successful developed according to the problem-based learning model to improve the ability of students to think critically. Problem-based learning-based E-modules are very feasible to be used in the process of learning activities in order to improve students' critical thinking skills. E-module of additives and addictive substances based on problem-based learning has been effective in improving the ability of students to think critically which is marked by an increase in students' pretest and posttest scores, and based on the average result of the N gain score of 0.76 which is included in the very decent category